Residential preference of young households in unplanned neighbourhood in Kano Metropolis, Nigeria - Abdu, Ado; Hashim, Ahmad Hariza (Researchjournali, 2016)
Housing is one of the human basic needs that provide security and neighbourhood facilities and services. Preference for housing attributes among young households is an important decision that points to their future residential needs. This study examined residential preference households in unplanned neighbourhoods in Kano metropolis, Nigeria. Data for was collected from 364 respondents using structured questionnaire from three unplanned neighbourhoods of Kano. Descriptive statistics of the households’ characteristics shows that the respondents aged between 30 – 45 years, 5 – 7 household members, low monthly income, lived in houses with few rooms and with length of residence between 3 to 5 years. Analysis shows that the respondents had high level of preference for housing features, housing amenities, housing conditions, housing safety and security and neighbourhood amenities, and moderate preference for neighbourhood facilities and accessibility factors. Based on the analysis, it can be concluded that the young households in the study area had high preference for housing attributes than neighbourhood attributes with exception of neighbourhood amenities. For future housing policies and programmes toward planned housing provision for young households living in unplanned neighbourhoods need to consider characteristics of the households and their housing and neighbourhood attributes’ preferences.